Implementasi Straregi Pembelajaran Kooperatif Think Pair Share (TPS) Pada Mata Pelajaran Pendidikan Agama Islam - Mulyono Mulyono; Sunhaji Sunhaji; Wahab Wahab (Institut Agama Islam Negeri Purwokerto, 2021)
One of the problems that hit education in Indonesia is the low quality of the learning process, such as inappropriate teacher teaching models and the lack of student motivation in the learning process. So it is necessary to have the right method in the process of these activities to be more active, effective and can increase the thinking power of students. Think Pair Share Strategy (TPS) is one of the learning methods that need to be used in teaching and learning activities, because the think pair share strategy is designed to invite students to seek answers to a question from a concept through a group. This is because in the teaching and learning process in schools that teachers often use the lecture and question and answer method (conventional), then the ability of students to ask questions or ask for help from the teacher is still not optimal. Through think pair share cooperative learning in Islamic Religious Education (PAI) subjects, it is hoped that students can be actively involved during the learning process. The purpose of implementing the strategy this is to find out the implementation of think pair share cooperative learning strategies in Islamic Religious Education subjects, and to determine the activeness of students when implementing think pair share cooperative learning strategies in Islamic Religious Education subjects. Keywords Cooperative Learning; Think Pair Share Strategy; Islamic Religious Education Abstrak Salah satu permasalahan yang melanda pada pendidikan di Indonesia adalah rendahnya mutu proses pembelajaran, seperti model mengajar guru yang tidak tepat dan kurangnya motivasi peserta didik dalam proses belajar. Sehingga perlu adanya metode yang tepat dalam proses kegiatan tersebut agar lebih aktif, efektif serta dapat meningkatkan daya pikir bagi peserta didik. Strategi Think Pair Share (TPS) merupakan salah satu metode pembelajaran yang perlu digunakan dalam kegiatan belajar mengajar, karena strategi think pair share ini dirancang untuk mengajak peserta didik mencari jawaban terhadap suatu pertanyaan dari suatu konsep melalui suatu kelompok. Hal ini disebabkan dalam proses belajar mengajar disekolah bahwa guru lebih sering menggunakan metode ceramah dan tanya jawab (konvensional), kemudian kemampuan peserta didik untuk bertanya atau meminta bantuan dari guru masih belum optimal. Melalui pembelajaran kooperatif tipe think pair share pada mata pelajaran Pendidikan Agama Islam (PAI), diharapkan dapat membuat peserta didik terlibat aktif pada saat proses pembelajaran berlangsung. Tujuan dari penerapan strategi TPS ini adalah untuk mengetahui penerepan strategi pembelajaran kooperatif think pair share pada mata pelajaran Pendidikan Agama Islam, dan untuk mengetahui keaktifan peserta didik pada saat penerapan strategi pembelajaran kooperatif tipe think pair share pada mata pelajaran Pendidikan Agama Islam. Kata Kunci Pembelajaran Kooperatif; Straregi Think Pair Share; Pendidikan Agama Islam